Socialização organizacional em uma IFES mineira em tempos de Reuni - Andrade, Diego César Terra de (2011)
The organizational socialization is seen as a complex process to be described and conducted, particularly because it involves both subjective and objective elements. This lecture was held in a Federal Institution of Higher Education (IFES), with technical and administrative staff and teachers, in order to: identify the perception of the servants about the level of organizational socialization; assess whether there is, among the technical and administrative staff and teachers, difference on the level of organizational socialization; verify if the level of organizational socialization varies according to the time of employment in the institution; and observe whether the level of organizational socialization varies as to the department or sector occupancy. Under the background and justification for this work, there is an increase in the number of IFES servants, arising from its accession to the Program to Support Expansion and Restructuring of Federal Universities - REUNI. The theoretical focus of the Organizational Socialization of the Contents and Information was used to base the research. The data collection instrument was the Organizational Socialization Inventory (ISO), consisting of 45 items that had been validated and adapted to the Brazilian public administration context by Borges et al. (2010). Responses were collected via an online survey, a total of 285 valid questionnaires, which were subject to factor analysis based on the technique of principal components (principal components) with orthogonal rotations - Varimax. In conclusion, taking into account the objectives of this study, it was found that the process of organizational socialization, in general, has been occurring efficiently in the IFES searched. Positively highlighting competence, as the hypothetical factor. In regards to the comparison of teachers and administrative staff occupational groups, there are no significant differences in the factors obtained, except for the domain of language. When checking whether the level of organizational socialization varies by length of time of employment in the institution, the Politics and History of the Organization factors were assessed and showed statistically significant and positive correlations, although modest in magnitude. However, the Competence factor presented negative and significant correlation, taking into consideration the time of employment in the institution. Finally, when observing if the level of organizational socialization varies as to the departmental and sector occupancy it was not possible to reach a conclusion due to the heterogeneity of the results of the dendrogram, which supports the initial indication of efficiency in the use of staff of the University.